Tungsten oxide nonvolatile memory devices using photothermal in-situ oxidation method - Shim, Jaeho; Park, Junghoon; Kwon, Kyungmok; Lee, Kyu Seung; Son, Dong Ick; Yu, Kyoungsik (ELSEVIER, 2020)
The tungsten oxide nonvolatile memory devices were fabricated using the photothermal in-situ oxidation method. The photothermal in-situ oxidation method can monitor the oxidation process in real time. Raman spectra revealed that tungsten oxides were formed by thermal oxidation. The ON/OFF ratio of the current bistability for the device was as large as similar to 10(2) at a 2 V reading voltage, and the cycling endurance of the ON/OFF switching for the devices was stable without noticeable degradation. Memory mechanisms for device are described using fitted the I-V curves. (C) 2020 Elsevier B.V. All rights reserved.